WHO ATTENDS CHRISTMAS MARKETS AND WHY? : ANALYSIS OF VISITOR STRUCTURE AND MOTIVATION FOR ATTENDING TWO CHRISTMAS MARKETS IN CROATIA (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
There are various motives for visiting a festival or an event. Motivations explain why people behave in a certain way and are therefore of particular interest in the context of meeting consumer expectations and needs. In this paper, the authors investigate the motives for attending two increasingly popular Christmas Markets in Croatia. The study compares the demographic structure of visitors, their travel behaviour and motivation for visiting the two markets and determines the level of their satisfaction and intentions for future behaviour. The overall aim is to identify visitors' needs and help destination managers organise activities that appeal to the target market. To this end, the authors have conducted desk and field research. Empirical research was conducted on the samples of Christmas Market visitors in Zagreb and Karlovac. The samples were selected using the convenience sampling method. Data analysis was performed using descriptive, inferential and multivariate statistics. The results of the research show that the travel behaviour of visitors and their motives for coming to the Christmas Markets differ, as well as their satisfaction level and loyalty. However, for both fairs a strong link was found between the visitors’ satisfaction with the visits and their intentions to revisit the two markets, recommend them, and share their experiences. This study makes a small contribution to the field of consumer behaviour by enhancing our understanding of the motivations for visiting different tourist events. The findings of this study may benefit festival and event managers by helping them deliver relevant customer experiences.